Health Issues of Adolescent Girls Student of Kalinga Institute of Social Sciences (KISS), Bhubaneswar, Odisha - Anupama Bhoi, Dr Manoj Kumar Behera (International Journal of Advanced Science and Technology, 2020)
Although the census 2011 enumerate the total population of scheduled Tribe at 10, 42, 18,034 persons Constitution 8.6 percent of the population of the Country the tribal communities in India. The Government of India in its Draft National Tribal policy 2006 records 698 scheduled Tribe in India As per the Census of India 2011, the number of individual groups notified as scheduled Tribe is 705.While it is not possible to provide detailed description of the demographic futures and socio economic status of each of these tribal groups. The state of Orissa Occupies a unique position in the Tribal map of India having 62 scheduled tribes including 13 primitive tribes .Odisha is the one of the most fascinating ethnographic State in India The background of every research tends to discover the truth of reality. The present research aims to study the tribal adolescent health issues and health practices in Kalinga Institute of Social Sciences (KISS).Bhubaneswar, Odisha. It analyse the effectiveness of the current health system for bringing awareness on their current health status. The study shows that adolescent girls suffering different diseases. poverty, economic dependence,socio-cultural constraints, lack of education, knowledge, awareness restricts on getting the best related awareness and benefits currently availed by state as well as central government. It has been observed that the health awareness among the primitive tribal girls increasing gradually. Though health awareness is gradually increasing due to lack of proactive approach towards the adolescent health is degrading the health conditions of the tribal adolescent girls in KISS.